(untitled) (Research, Society and Development, 2021)
The present work grants a study of technical development under a differentiated aspect where an extra tire was added to the standard double axle recommended by the Brazilian traffic calculation norms. The number N generated a triple axle, and a comparative study was made relating the balance load standardized in Brazilian balance laws for each type of axis and the damage generated on the pavement, measuring the results on a pavement chosen as a model, usually used on Brazilian highways. We verified through computer software, which uses the methodology of the theory of finite elements, supervised by the inspection bodies of the National Department of Transport infrastructure, proving if a larger amount of cargo generates the same damage to the pavement without jeopardizing its useful life, which was initially designed to last ten years.